Anatomy of failure : philosophy and political action - Feltham, Oliver (Bloomsbury Academic, 2013)
Modern liberalism begins in the forgetting of the English Revolution. Anatomy of Failure seeks to right that wrong by exploring the concept of political action, playing its history against its philosophy. The 1640s are a period of institutional failure and political disaster: the country plunges into civil war, every agent is naked. Established procedures are thrown aside and the very grounds for action are fiercely debated and recast. Five queries emerge in the experience of the New Model Army, five queries that outline an anatomy of failure, isolating the points at which actors disagree, con.